The Impact of COVID-19 in Older People in Portugal: Results from the Survey of Health, Ageing and Retirement (SHARE) - Novais, Filipa (2021)
Introduction: In March 2020, the World Health Organization declared COVID-19 as a pandemic, and Portugal reported its initial cases. In this study, we aimed to determine the impact of COVID-19 on Portuguese individuals aged over 60 years old.Material and Methods: We performed a cross-sectional study using data from the Survey of Health, Ageing and Retirement in Europe (SHARE 8: COVID-19 Survey). We selected a sample of 1080 noninstitutional Portuguese individuals aged ≥ 60 years.Results: The study sample consisted of 605 (56%) women and 475 (44%) men, with a mean age of 70 ± 9.1 years. In total, 80% of the participants experienced higher levels of anxiety, 73% felt more depressed and 30% experienced additional sleep problems comparedto the period before the pandemic. Interestingly, there were no statistically significant differences between the sexes or the two selected age groups (60 - 74 and over 75 years old) regarding the incidence of these changes. Only 23%, of those that were interviewed maintained their walking routines. In addition, only 8% of the participants continued visiting family members as frequently as before. While 8% of the participants were refused some form of medical treatment, 56% claimed that they experienced healthcare delays. However,only 15% of the participants reported that their health status worsened during the pandemic.Discussion: The pandemic has had a significant impact on Portuguese individuals aged ≥ 60 years; which is in agreement with the findings of previous international studies. It changed the participants’ routines and increased their anxiety and depression levels. Despite the deterioration of healthcare services, most participants did not experience worsening of their health status.Conclusion: In conclusion, a COVID-19 pandemic had a significant impact on the elderly population, particularly regarding their mental health.